OROO'GAME-BASED LEARNING MOBILE APPLICATION - Lee, Heng Keat (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This paper describes the game-based learning techniques in developing a learning game to teach Oroo signs to Young Penans. This will help in retaining and preserving the Oroo ' language. from Young Penans who once rapidly losing this knowledge. Younger generations are more interested in using ICTs , for communication. Hence, this proposed solution is going to develop a fully functional game. for Penan s children to learn Oroo s sign language. This proposed game-based learning application will be developed in Android platform by using the waterfall in game development life-cycle.